STRATEGI PEMASARAN PRODUK KEUANGAN SYARIAH DALAM MENARIK MINAT NASABAH STUDI KASUS BSI KCP. PASAR KLIWON SURAKARTA - Rifai, Fajar; Sulistyowati, S; Nissa, Izzun Khoirun (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
ABSTRACT : Strategic planning is a comprehensive, integrated, and guiding plan for a company to achieve its goals. It involves not only operational planning but also strategic planning, planning, execution, and management of resources to ensure the success of the company. Strategic planning is also a response to changing business environment and competitiveness. Bank Syariah Indonesia (BSI) implements various strategic plans to increase the market share of its syariah products. These include traditional methods, such as the Surat Permohonan and Flyering, and door-to-door strategies. Traditional methods involve preparing the product for sale and distributing flyers to potential customers. Door-to-door strategies involve delivering the product to customers at home or in the office, fostering personal connections between the bank and the customer. In the modern era, the use of technology, data, and consumer behavior has become increasingly important. The use of technology in marketing strategies enables companies to create, launch, and optimize marketing campaigns more effectively and efficiently. Data analysis is a crucial part of data management, as it helps in gathering, analyzing, and modeling data. Bank Syariah Indonesia (BSI) has implemented various data analysis methods to enhance its marketing efforts and customer satisfaction. In conclusion, strategic planning is a crucial aspect of a company's success, and BSI has implemented various strategies to achieve its goals. Keywords : Bank Syariah Insonesia (BSI), Marketing strategy of Islamic financial products, customer interest in Islamic financial products.